Clock genes and cancer development in particular in endocrine tissues. Issue 6 (June 2019) - Angelousi, Anna; Kassi, Eva; Ansari-Nasiri, Narjes; Randeva, Harpal; Kaltsas, Gregory; Chrousos, George
Abstract : Circadian rhythms at a central and peripheral level are operated by transcriptional/translational feedback loops involving a set of genes called 'clock genes' that have been implicated in the development of several diseases, including malignancies. Dysregulation of the Clock system can influence cancer susceptibility by regulating DNA damage and repair mechanisms, as well as apoptosis. A number of oncogenic pathways can be dysregulated via clock genes' epigenetic alterations, including hypermethylation of clock genes' promoters or variants of clock genes. Clock gene disruption has been studied in breast, lung and prostate cancer, and haematological malignancies. However, it is still not entirely clear whether clock gene disruption is the cause or the consequence of tumourigenesis and data in endocrine neoplasms are scarce. Recent findings suggest that clock genes are implicated in benign and malignant adrenocortical neoplasias. They have been also associated with follicular and papillary thyroid carcinomas and parathyroid adenomas, as well as pituitary adenomas and craniopharyngiomas. Dysregulation of clock genes is also encountered in ovarian and testicular tumours and may also be related with their susceptibility to chemotherapeutic agents. The most common clock genes that are implicated in endocrine neoplasms are PER1, CRY1 ; in most cases their expression is downregulated in tumoural compared to normal tissues. Although there is still a lot to be done for the better understanding of the role of clock genes in endocrine tumourigenenesis, existing evidence could guide research and help identify novel therapeutic targets aiming mainly at the peripheral components of the clock gene system.